Chloride transport and homeostasis in plants - Harverth Silva-Herrera; Stefanie Wege; Bastian Leander Franzisky; Namrah Ahmad; M. Rob G. Roelfsema; Christoph-Martin Geilfus (Quantitative Plant Biology, 2025)
The micronutrient chloride (Cl―) plays key roles in plant physiology, from photosystem II and vacuolar ATPase activity to osmoregulation, turgor maintenance and drought resilience, while also posing toxicity risks at high concentrations. This review examines Cl― uptake, transport and homeostasis, focussing on adaptations balancing its dual roles as a nutrient and toxicant. Key transporters, including NPF, SLAH, ALMT, CLC and CCC families, mediate Cl― fluxes to maintain ionic balance and prevent toxicity. Plants employ strategies such as selective uptake and vacuolar compartmentalization to cope with high salinity. Cl― also influences nitrogen-use efficiency and plant productivity. Advances in transporter biology reveal the role of Cl― in water-use efficiency, drought resilience and stress adaptation.